Do Social Networks Prevent or Promote Bank Runs? - Hubert János Kiss; Ismael Rodriguez-Lara; Alfonso Rosa-García (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
We report experimental evidence on the effect of observability of actions on bank runs. We model depositors' decision-making in a sequential framework, with three depositors located at the nodes of a network. Depositors observe the other depositors' actions only if connected by the network. Theoretically, a sufficient condition to prevent bank runs is that the second depositor to act is able to observe the first one's action (no matter what is observed). Experimentally, we find that observability of actions affects the likelihood of bank runs, but depositors' choice is highly influenced by the particular action that is being observed. Depositors who are observed by others at the beginning of the line are more likely to keep their money deposited, leading to less bank runs. When withdrawals are observed, bank runs are more likely even when the mere observation of actions should prevent them.
Keywords: C70; C91; D80; D85; G21; 330; bank runs; social networks; coordination failures; experimental evidence